Studi Kasus Tentang Gaya Hidup Hedonisme Mahasiswa Bimbingan dan Konseling Angkatan 2011 Universitas Ahmad Dahlan - Trimartati, Novita (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2014)
This research was motivated by the phenomenon hedonistic lifestyle among students, it is possible the student guidance and counseling. This study aims to determine the cause of the lifestyle of hedonism student guidance and counseling class of 2011 at the Ahmad Dahlan University Yogyakarta. This research was conducted using qualitative research case study, which explores in more depth about the problems associated with the lifestyle of hedonism student guidance and counseling class of 2011 at the Ahmad Dahlan University Yogyakarta. A researcher using purposive sampling for the subjects to be studied attention to their special characteristics or properties owned. Researchers get 3 men and 2 women who were subjects in this study. Results of the research have shown that students hedonistic lifestyle guidance and counseling class of 2011 was motivated by external factors, namely family and friends association. Disharmony in the family and lack of attention, affection, regulations both within families and communities create pressure within the individual, and the persuasion of friends, making its difficult escape from the snare lifestyle of hedonism. Research results helpful in providing information for parents who have a child as a student of the hedonistic lifestyle of students, besides the results of research can help parents prevent behavior for a lifestyle of hedonism.